Association between food management behaviours and household food waste among working adults in health campus, Universiti Sains Malaysia, Kubang Kerian, Malaysia - Tahir, Nurain Mohd (Universiti Sains Malaysia, 2025)
Recent research has begun to demonstrate the vital role of daily food provision practices in influencing household food waste. Food waste occurs throughout the food chain, yet homes are the primary contributor. The purpose of this research, is to investigate the association between food management behaviours and household food waste among working adults at Universiti Sains Malaysia in Kubang Kerian, Malaysia. In this study, a sample size of 215 working adults from the School of Health Sciences, School of Medicine, and School of Dentistry was recruited using stratified random sampling based on inclusion criteria. However, only 180 responses were gathered and analyzed with SPSS version 29.0. Among the five investigated factors, Food Storage Behaviour (FSB) (p=0.876) and Leftover Consumption Behavior (LCB) (p=0.764) were not significantly associated with household food waste (p > 0.05). However, Food Purchase Planning Behaviour (FPB) (p < .001), Food Purchase Behaviour in Store (FPBI-S) (p < .001), and Food Planning Preparation Behaviour (FPPB) (p=.039), demonstrated significant associations. The findings of this study, as well as previous studies by other researchers, can be utilized to drive effective interventions that focus on specific food waste situations and interactions in greater depth. The intervention could particularly help to shift the focus from analysis to solutions.